2021
DOI: 10.1007/s00404-021-06320-3
|View full text |Cite
|
Sign up to set email alerts
|

The optimal time for the initiation of in vitro fertilization and embryo transfer among women with atypical endometrial hyperplasia and endometrial carcinoma receiving fertility-sparing treatment

Abstract: Objective To explore the optimal time for initiating in vitro fertilization and embryo transfer (IVF-ET) in women with complete remission after fertility-sparing treatment for grade I endometrial cancer (EC) or atypical endometrial hyperplasia (AEH). Patients and methodsYoung women who demonstrated complete remission after fertility-sparing treatment for grade I EC or AEH and underwent IVF-ET treatment were included. A generalized estimating equation (GEE) was used to compare the outcomes of controlled ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…A further 12 articles were added from the reference lists. Thirty-two articles, comprising 371 patients with recurrent AH and ECG1, finally met the inclusion criteria for this review [ 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 ]. Among these, six cases were excluded because of grade 2–3 histology.…”
Section: Resultsmentioning
confidence: 99%
“…A further 12 articles were added from the reference lists. Thirty-two articles, comprising 371 patients with recurrent AH and ECG1, finally met the inclusion criteria for this review [ 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 ]. Among these, six cases were excluded because of grade 2–3 histology.…”
Section: Resultsmentioning
confidence: 99%
“… 23 , 24 Nevertheless, evidence suggests that patients may choose IVF three months after achieving complete remission. 25 In this case report, controlled ovulation stimulation was performed immediately on patients after complete remission to minimize the time window between disease remission and recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort published by Ziyi Song et al. ( 47 ) found that initiation of IVF 3 months after CR demonstrated a trend toward an increased number of oocytes, resulting in better controlled ovarian hyperstimulation outcomes for patients. On the other hand, endometrial lesions recurrence is a clear factor affecting pregnancy success ( 18 , 19 ).…”
Section: Factors Affecting Pregnancy Outcomes Of Art Treatment In Aeh...mentioning
confidence: 99%